The conjugated antimetabolite 5-FdU-ECyd and its cellular and molecular effects on platinum-sensitive vs. -resistant ovarian cancer cells in vitro - Schott, Sarah (OncoTarget, 2017)
Background: Resistance to platinum-based chemotherapy is a clinical challenge in the treatment of ovarian cancer (OC) and limits survival. Therefore, innovative drugs against platinum-resistance are urgently needed. Our therapeutic concept is based on the conjugation of two chemotherapeutic compounds to a monotherapeutic pro-drug, which is taken up by cancer cells and cleaved into active cytostatic metabolites. We explore the activity of the duplex-prodrug 5-FdU-ECyd, covalently linking 2'-deoxy-5-fluorouridine (5-FdU) and 3'-C-ethynylcytidine (ECyd), on platinum-resistant OC cells. Methods: In vitro assays and RNA-Sequencing were applied for characterization of 5-FdU-ECyd treated platinum-sensitive A2780 and isogenic platinum-resistant A2780cis and independent platinum-resistant Skov-3-IP OC cells. Results: Nano molar 5-FdU-ECyd concentrations induced a rapid dose-dependent decline of cell viability in platinum-sensitive and -resistant OC cells. The effect of 5-FdU-ECyd was accompanied by the formation of DNA double strand breaks and apoptosis induction, indicated by a strong increase of pro-apoptotic molecular markers. Moreover, 5-FdU-ECyd efficiently decreased migration of platinum-resistant OC cells and inhibited clonogenic or spheroidal growth. Transcriptome analysis showed early up-regulation of CDKN1A and c-Fos in both, platinum-resistant and -sensitive cells after 5-FdU-ECyd treatment and de-regulation of distinct cellular pathways involved in cell cycle regulation, apoptosis, DNA-damage response and RNA-metabolism. Combined treatment of 5-FdU-ECyd and cisplatin did not show a synergistic cellular response, suggesting the potential use of 5-FdU-ECyd as a monotherapeutic agent. Conclusion: Our data provide novel mechanistic insight into the anti-tumor effect of 5-FdU-ECyd and we hypothesize that this duplex-prodrug could be a promising therapeutic option for OC patients with resistance to platinum-based chemotherapy.